2023
DOI: 10.3390/su151612285
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Factors Influencing the Blast Resistance of Reinforced Concrete Columns Based on Grey Relation Degree

Abstract: Reinforced concrete (RC) column is an important load-bearing component in building structures. In order to study the blast resistance of RC columns, the numerical simulation model was verified based on the field test data, and the ANSYS/LS-DYNA 2020R2 software was used to expand the working conditions. The sensitivity analysis method of grey relation degree was used to study the effects of factors, such as the diameter of longitudinal reinforcement, number of longitudinal reinforcement, the diameter of the sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…(1) Spacing of the transverse bars (s t ); Wu et al [35] used the gray relation method to assess the influence of various parameters on the dynamic response of square RC columns under a close-in explosion. It was shown that the spacing of the transverse bars (s t ) has the most important impact on the mid-span peak displacement of RC columns.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(1) Spacing of the transverse bars (s t ); Wu et al [35] used the gray relation method to assess the influence of various parameters on the dynamic response of square RC columns under a close-in explosion. It was shown that the spacing of the transverse bars (s t ) has the most important impact on the mid-span peak displacement of RC columns.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the parameters studied in [35], the influence of the load eccentricity is also investigated in this work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations